2012
DOI: 10.3945/ajcn.111.017277
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of macronutrient content in 2 energy-restricted diets on cardiovascular risk factors and adipose tissue cell size in moderately obese individuals: a randomized controlled trial

Abstract: In comparison with the LC-CONV diet, the LC-P-LGI diet was associated with improvement in some cardiometabolic risk factors and greater reduction in adipocyte size. Profiles of genes involved in inhibiting adipogenesis and angiogenesis, but increasing apoptosis, were correlated with decreased adipocyte size. This study provides insight into the adipose tissue-remodeling changes that induce regulation of adipocyte size during dietary weight loss. This trial was registered at clinicaltrials.gov as NCT01312740.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 46 publications
1
42
1
Order By: Relevance
“…Taken together, in our overweight and obese subjects, IL-6 has negative effects on metabolism, and 12-week lifestyle modification decrease circulating IL-6 levels, insulin levels and HOMA-IR. A previous study that investigated the effect of a 16-week period of dietary restriction on circulating levels of MIP-1β, G-CSF, and VEGF found that the levels did not change significantly [6]. Compared with the results of our study here, the degree of weight-loss was smaller in the previous study, which may have caused a different effect on the inflammatory condition.…”
Section: -24]contrasting
confidence: 94%
See 1 more Smart Citation
“…Taken together, in our overweight and obese subjects, IL-6 has negative effects on metabolism, and 12-week lifestyle modification decrease circulating IL-6 levels, insulin levels and HOMA-IR. A previous study that investigated the effect of a 16-week period of dietary restriction on circulating levels of MIP-1β, G-CSF, and VEGF found that the levels did not change significantly [6]. Compared with the results of our study here, the degree of weight-loss was smaller in the previous study, which may have caused a different effect on the inflammatory condition.…”
Section: -24]contrasting
confidence: 94%
“…Several previous studies have revealed that weight-loss is an effective way to reduce the levels of many types of inflammatory substances (i.e., C-reactive protein [CRP], tumor necrosis factor alpha [TNF-α], interleukin-6 [IL-6], interleukin-1 beta [IL-1β], monocyte chemoattractant protein 1 [MCP-1] etc.) in obese individuals [5][6][7][8][9]. Numerous types of inflammatory substances have been found and most of these levels are known to increase in obesity.…”
mentioning
confidence: 99%
“…The consequences on adipose tissue biology of such diets differing by their protein composition are not well known. In addition to a small loss of fat mass (10%), we identified an important reduction of adipocyte weight (30 -40%), in agreement with the relevance of adipocyte size as an important cellular obesity phenotype (38). Unfortunately, we could not find any difference for this parameter between the spread and pulse groups whatever the protein source.…”
Section: Discussionsupporting
confidence: 82%
“…The association between gene expression changes in adipose tissue and modification of adipocyte size, an important marker of obesity phenotype, has been recently described during restriction diet trials (38). We further characterized adipose tissue gene expression and determined adipocyte size before and after dietary intervention.…”
mentioning
confidence: 92%
“…Nevertheless, it is important to note that weight loss in obese individuals does not appear to be accompanied by a decreased ABCG1 expression in AT, as it could have been initially expected. Indeed, gene expression analysis of subcutaneous AT from obese patients following caloric restriction [11][12][13][14] or surgery 15 did not reveal any reduction of ABCG1 expression in AT after weight loss but instead detected an upregulation of this pathway in some cases. 16,17 These intriguing data suggest that ABCG1 can exert a more complex role in AT than that recently identified by us in adipocytes.…”
mentioning
confidence: 97%